Pengembangan strategi pembelajaran kolaboratif dalam Tim mahasiswa Kalimantan Barat - Rasyid, Harun; M. Asrori, M. Asrori (LPMPP Universitas Negeri Yogyakarta, 2006)
Unparalleled technological advances, escalating global competition, and other forms of workplace turbulence have led to dramatic changes in the American economic arena. Today, leaders in business and industry cite the ability to work collaboratively as requisite to success in the worldwide economic environment. However, research indicates that many students arrive on the college campus with little or no experience in working as part of a team. Moreove, employers indicate the today's entry-level workers lack this critical wokplace competency. Through skillfull guidance, however, post secondary educators can implement strategies that will help students learn how to work successfully as part of team.The objective of the present reseach is an establishment of the collaborative teamwork learning strategyas well as its for teacher, students, or bath of them. Therefore, the present reseacrh is carried out by (1) need assessment about the beginning level of student;s collaborative teamwork; (2) need assessment about teaching strategies that really carried out by lecturrers in order to develop students' coollaborative team work capacity; (#) to organize the collaborative teamwork teaching strategy; and (4) emperical validation through field try out at the three univesity (FKIP Tanjungpura University, STKIP-PGRI,and Tarbiyah Faculty of Muhammadiyah University)